2005
DOI: 10.1007/s10461-005-3896-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Dimensions of HIV Stigma and Psychological Distress Among Asians and Pacific Islanders Living With HIV Illness

Abstract: Asians and Pacific Islanders (APIs) living with HIV/AIDS in the US are particularly vulnerable to HIV-related stigma largely due to ingrained socio-cultural norms that strongly associate HIV transmission with activities perceived to be immoral. This cross-sectional study examined the relationship between five HIV-stigma factors and psychological distress among 54 HIV-seropositive APIs. Social Rejection, Negative Self-Worth, Perceived Interpersonal Insecurity, and Financial Security were all significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
3
38
1
1
Order By: Relevance
“…The Asian sex workers thus occupied a more privileged echelon within the Collective Black stratum, a position that correlated with moderate (as opposed to high) HIV risk. As we discussed earlier, even slight differences in the rank ordering of communities indicate a differential participation along a scale of graded 18 Immigrants, in fact, are often viewed in studies as being more vulnerable to HIV infection than nonimmigrants, although immigrants are usually compared only with non-immigrants in the same racial or ethnic population (Bhattacharya, 2004;Kang, Rapkin, Remien, Mellins, & Oh, 2005;Kang, Rapkin, Springer, & Kim, 2003). 19 Because this model appears to be at least partially based on the Brazilian model of pretos, pardos, and brancos, where the middle stratum of pardos comprises those who are partially of European descent, referring to this category as Honorary Whites seems apropos for this middle stratum in South American and Latin American contexts but is not necessarily applicable to U.S. contexts.…”
Section: Racial Marginalization and Sex Workmentioning
confidence: 99%
“…The Asian sex workers thus occupied a more privileged echelon within the Collective Black stratum, a position that correlated with moderate (as opposed to high) HIV risk. As we discussed earlier, even slight differences in the rank ordering of communities indicate a differential participation along a scale of graded 18 Immigrants, in fact, are often viewed in studies as being more vulnerable to HIV infection than nonimmigrants, although immigrants are usually compared only with non-immigrants in the same racial or ethnic population (Bhattacharya, 2004;Kang, Rapkin, Remien, Mellins, & Oh, 2005;Kang, Rapkin, Springer, & Kim, 2003). 19 Because this model appears to be at least partially based on the Brazilian model of pretos, pardos, and brancos, where the middle stratum of pardos comprises those who are partially of European descent, referring to this category as Honorary Whites seems apropos for this middle stratum in South American and Latin American contexts but is not necessarily applicable to U.S. contexts.…”
Section: Racial Marginalization and Sex Workmentioning
confidence: 99%
“…HIV-related stigma has been shown to compromise physical, psychological, and social health [27], which in turn affects QOL of PLWHA through multiple ways including interference in daily routine as well as the person's intention and ability to access health care services [28]. In a multi-site study, Holzemer et al [29] found that perceived stigma explained a significant amount of variance in QOL among PLWHA in addition to that explained by HIV-related symptoms and severity of illness.…”
Section: Introductionmentioning
confidence: 99%
“…PWH have reported numerous mental and physical effects from stigma, including fear, isolation, anxiety, depression, and poor psychological functioning (Barroso & Powell-Cope, 2000;Berger, Ferrans, & Lashley, 2001;Clark, Lindner, Armistead, & Austin, 2003;Courtenay-Quirk, Wolitski, Parsons, & Gomez, 2006;Kang, Rapkin, Remien, Mellins, & Oh, 2005;Relf, 2005;Sowell et al, 1997;Vanable, Carey, Blair, & Littlewood, 2006). For example, HIV-infected mothers who report high levels of HIV-related stigma score significantly lower on measures of physical, psychological, and social functioning, and higher on measures of depression, compared to mothers who report low levels of HIVrelated stigma (Murphy, Austin, & Greenwell, in press).…”
Section: Introductionmentioning
confidence: 99%